INFLUENCE OF VIRAL LIVER DISEASES ON THE STATE OF THE ORAL CAVITY. (LITERATURE REVIEW) - Alieva, Nazokat Muratjonovna; Tolipova, Mokhinur Azizovna (Innovative Development in Educational Activities, 2022)
Chronic hepatitis today occupy a significant place in the general human pathology, causing significant social and economic damage to society. In the structure of pathological conditions associated with liver damage, the proportion of viral lesions is progressively increasing. Currently, at least 9 types of human hepatits are known (A, B, C, D, E, G, F, TT, Sen), among which parenteral viral hepatitis deserves special attention, characterized by severe and chronic forms with an outcome in liver cirrhosis and hepatocellular carcinoma. In assessing the state of dental health of patients, an important place is occupied by viral lesions of the liver. At the same time, dentists and doctors of other specialties do not pay due attention to the state of the oral cavity in liver diseases [1,2,11,13]. There are very few developments on dental tactics for managing patients with hepatitis. In countries with a high level of dental services, experience has also not been accumulated on this problem. Widespread hepatitis, in particular hepatitis B, requires in-depth dental research.